PENGARUH HIPNOTERAPI TERHADAP PASIEN YANG MENGALAMI GANGGUAN KECEMASAN : LITERATURE REVIEW - Gerald Vico Ananda; Dini Nur Alpiah (JURNAL ILMIAH RESEARCH STUDENT, 2024)
Background : Anxiety is a common psychological disorder that can have a detrimental impact on a person's life. Anxiety disorders usually occur due to stress such as facing exams, job interviews, or making important decisions. Hypnotherapy is one of the many therapies used to treat anxiety disorders. Purpose : This review of the research aims to evaluate how hypnotherapy affects individuals with anxiety problems. Method : The first step in analyzing literature is to search for journals by utilizing national and international web sources such as Google Scholar. Results : Findings from the 5 selected journal articles, it can be concluded that although anxiety has various reasons, hypnosis is a technique that is generally useful for reducing anxiety levels. Conclusion : Hypnotherapy is an effective method for reducing anxiety. Hypnotherapy is useful in treating a person's mental health. It is recommended that the hypnotic approach in mental therapy be studied more deeply in order to treat patients with anxiety disorders better.